The Influence of Safety Communications and Safety Promotion Policies on Safety Performance among Nurses in The Emergency Department at a Tertiary Hospital in Surabaya, Indonesia - Berliana, Ratih; Widajati, Noeroel; Saridewi, Nurhayati; Dwiyanti, Endang (Folia Medica Indonesiana, 2022)
Highlights: • To reduce the occurrence of work-related accidents, the application of occupational safety and health principles in work activities is necessary. • This research analyzed the safety communications and safety promotion policies on the safety performance among nurses. • Safety communications have influence on safety performance, while safety promotion policies have no influence on safety performance. Abstract: The application of the occupational safety and health principles in work activities is expected to reduce the occurrence of work-related accidents. This research was conducted in the Emergency Department of a tertiary hospital of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in 2019 and aimed to determine the influence of safety communications and safety promotion policies on the safety performance among nurses. This research was a quantitative research with a cross-sectional design study. The population in this study were 208 emergency room nurses at Dr. Soetomo General Academic Hospital with a total sample of 68 people using a simple random sampling technique. The results showed that the correlation between safety communications variable with safety performance had a p-value of 0.035 (<0.05) and the correlation between safety promotion policies variable with safety performance had a p-value of 0.319 (>0.05), indicating that there was an influence of safety communications on safety performance, while there was no influence of safety promotion policies on safety performance among nurses in the Emergency Department of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia.